Preparation of unique landscape values register of Sámsonháza (Šámšonház) - Tóth, Enikő (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
The concept of unique landscape is defined by the Nature Conservation Law, in the 6th paragraph (3) point. This definition was taken over by the Hungarian Standard of 20381: 2009. The essential element of the definition is that the natural character and the landscape elements created by human activities also can be qualified as unique landscape. During my work I tried to make a register of Sámsonháza’s unique landscape values, in which the settlement has multiple disadvantages in Nógrád county, because of its location. It is lying in the val- ley of Kis-Zagyva. It is situated in a nationally disadvantaged position which indicates an unfavorable location that is free from industrial areas. However it is inhabited by Slovaks and Palóc-speaking peoples, who were settled in the 18th century. Their descendants are living there in a hilly, small stream crossed place, interspersed by forest patches. It is bounded by Ipoly, Mátra, Börzsöny, we can find there the ruins of Fejérkő-castle with varied landscapes surfaces. My goal was to research and record the nature’s unique landscape values within the border of administration area of Sámsonháza. After that I wanted to prepare the declaration of unique landscape value for each element, and make suggestions for their maintenance and method of survival. These conditions contribute the preservation of the image of Hungary’s unique surface, and ensure the enhancing competitiveness of the region. It is an appropriate base to prepare a country-wide register, which can ease the nature conservation cases, the protection and preservation of natural and cultural values, and the presentation of these values for the tourism with the government collaboration. I made my investigation by visiting these locations, with filling the individual data sheets, marking them on the maps, and expand them with photographs. This process is standardized by the Hungarian Standard 20381:2009. Before this site seeing operations I collected the needed information including the suitable maps from the settlement’s parish hall, from libraries, and internet. Finally I had to process the data and prepare the register with the documentation. After all I can appoint that in this small settlement, I found unique landscape values, which have great significance for the local people.
Keywords: unique landscape values; register; Nógrád county; TÉKA; Slovak; Palóc